2011
DOI: 10.1096/fj.11-187534
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into cellular alteration of prion by poly‐D‐lysine: the role of H2H3 domain

Abstract: Misfolding of the prion protein (PrP) is the central feature of prion diseases. The conversion of the normal α-helical PrP(C) into a pathological β-enriched PrP(Sc) constitutes an early event in the infectious process. Several hypotheses, involving different regions of the protein, endeavor to delineate the structural mechanism underlying this change of conformation. All current working hypotheses, however, are based on biophysical and modeling studies, the biological relevance of which still needs to be asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…As shown by the apparent contradiction between these models, a consensus has yet to be found that should be based on in vivo studies. In favor of the H2H3 hypothesis, we have previously shown that (i) H2H3 can be independently generated in an Escherichia coli system and retain its native secondary and tertiary structure (23), (ii) H2H3 is able to fibrillize and reproduce the oligomerization pathways of PrP (23,24), and (iii) in a cellular model of prion infection, polylysines are able to eliminate PK-resistant PrP through a direct interaction with H2H3 (25). These results led to the hypothesis that H2H3 could be the minimal region involved in the change of conformation of PrP.…”
Section: Prpmentioning
confidence: 99%
“…As shown by the apparent contradiction between these models, a consensus has yet to be found that should be based on in vivo studies. In favor of the H2H3 hypothesis, we have previously shown that (i) H2H3 can be independently generated in an Escherichia coli system and retain its native secondary and tertiary structure (23), (ii) H2H3 is able to fibrillize and reproduce the oligomerization pathways of PrP (23,24), and (iii) in a cellular model of prion infection, polylysines are able to eliminate PK-resistant PrP through a direct interaction with H2H3 (25). These results led to the hypothesis that H2H3 could be the minimal region involved in the change of conformation of PrP.…”
Section: Prpmentioning
confidence: 99%
“…An assignment of NMR peaks indicated that most of the perturbed peaks (Δδ > 0.10) were mapped onto the loop region connecting Helix 2 and Helix 3 (residues 180-200) (Figure 4(b,c)). As indicated in the previous study [8], this loop region composes a negatively charged patch to serve as a binding surface for poly-L-Lys. These results indicated that poly-L-His and poly-L-Lys share a common mechanism in inhibiting prion propagation which involves direct binding to a negatively charged surface of PrP C .…”
Section: Poly-l-his Directly Binds To Cellular Prion Proteinmentioning
confidence: 82%
“…This result ruled out the possibility that poly-L-His inhibits prion propagation through metal chelation. A previous study examining anti-prion mechanism of a positively charged poly-(amino acid), poly-L-Lys, indicated that a negatively charged surface of the Helix 2-Helix 3 region of PrP C (residues 169-230) is the specific site for poly-L-Lys binding [8]. In fact, the Helix 2-Helix 3 region has been suggested as an initiation site for the structural conversion of PrP toward PrP Sc [23][24][25][26] and is a major target for many anti-prion compounds [14,[27][28][29][30].…”
Section: Poly-l-his Directly Binds To Cellular Prion Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Because previous studies [32] reported that anti-prion activity of PLK correlates with its direct binding to PrP C , investigation on the possibility of PLR interaction with PrP C and its relevance to anti-prion activity of PLR is of interest. If this turns out to be the case, together with our findings demonstrated in this study, it is feasible to speculate that there exist multiple molecular events involved in PLR action to suppress prions.…”
Section: Discussionmentioning
confidence: 99%